Methodological approaches in graded dental ceramics - Gali, Sivaranjani (Dent Mater, 2024)
BACKGROUND: Functionally graded materials (FGM) with indistinct boundaries potentially eliminate the damaging stresses occurring at the interfaces. FGM applications in dental ceramics have enhanced their fatigue resistance and interfacial toughness. OBJECTIVES: This scoping review aims to map graded designs in dental ceramics, distinguish their methodological approaches with their material characteristics and properties, and understand the factors affecting the outcomes of each of the graded approaches. METHODS: A systematic electronic search was performed with the databases MEDLINE (PubMed), Scopus, Cochrane Library, EBSCO, and Google Scholar along with a manual search. RESULTS: About 2675 articles were initially found from all the searches with no date restriction till July 2023. After rejecting duplicates and based on exclusion criteria, about 52 articles were included. SIGNIFICANCE: Methodological approaches in grading such as glass-infiltration and silica-infiltration have been investigated on pre-sintered zirconia. The type of infiltration and the method of infiltrate application significantly influenced the phase transformation of zirconia, its microstructure, surface hardness, fracture toughness, flexural strength, wear, and fatigue strength of graded dental zirconia. Interlayers were accommodated between metal-ceramic and veneer-core all-ceramic layers. Fractions of zirconia-porcelain and alumina-porcelain showed high bending strength and better stress distribution. The results of finite element analysis studies predicted that using 10-layered graded layers reduced the stresses at the crown-cement-dentin interface.